DILEMATIS KODE ETIK PROFESI DAN PERANAN BACKGROUND KONSULTAN PAJAK DALAM MELAKUKAN TAX PLANNING - B41109096, Robby (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
Application of the code of professional Ethical conduct by the Indonesian Tax Consultants Association pose an ethical dilemma for any tax consultants. Besides trying to help taxpayers who have tax problems, tax consultant started his business as well as to fulfill his life. This study aims to determine the behavior of the X Tax Consultant in the face of professional ethics dilemma and see the X Tax Consultant role Background in conducting tax planning in accordance with the professional code of ethics. The data obtained are primary data collected using interviews, questionnaires, observation, and documentation. After it is processed and analyzed descriptively to get clear results. Results of the analysis in this study showed that the overall Tax Consultant X still behave ethically in dealing with ethical dilemmas. It's just that for some cases of X Tax Consultant is acting out of professional codes of ethics. This happens because of the demands of the work that exposes a consultant should be able to resolve a tax problem their clients so consultants are more likely to take the easy way to solve it. In addition, the work is too oriented to obtain the material is also a major cause of a consultant may violate professional codes of ethics. Thus it can be seen where the background role of tax consultants become an important capital to be able to help the X Tax Consultants in ethical behavior. Keywords: Dilemma Ethics, Code of Ethics, Ethical Conduct, Background, Tax Consultants, Tax Planning